Durable light-color antistatic master batch, fiber and preparation method of durable light-color antistatic master batch

By introducing polymer antistatic agents and metal nanoparticles into the antistatic fibers and blending them with silane coupling agents and dispersing agents, the existing antistatic fibers have been solved, and the antistatic effect with low addition, light color and long-term effect is achieved.

CN119592056APending Publication Date: 2025-03-11DONGHUA UNIV +1

Patent Information

Application Number
CN202411782160.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

During the use of existing antistatic fibers, there are problems such as dark color, large filling amount and poor durability, and it is difficult to achieve low addition amount, light color and long-term antistatic effects at the same time.

Method used

By introducing polymer antistatic agents and metal nanoparticles into the polymer matrix and blending them with silane coupling agents and dispersing agents, an effective conductive network is formed, reducing the amount of filler, while maintaining the light color of the fibers.

Benefits of technology

It realizes the formation of a complete conductive network under low addition amount, significantly improving antistatic properties, and the fibers are light in color, which is easy to dye and post-processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005173036810000141
    Figure BDA0005173036810000141
Patent Text Reader

Abstract

The invention relates to a durable light-color antistatic master batch, a fiber and a preparation method thereof. The durable light-color antistatic master batch comprises the following components in parts by mass: 1-20 parts of a macromolecular antistatic agent, 0-10 parts of metal nanoparticles, 3-5 parts of a dispersing accelerator, 0.3-0.5 part of a silane coupling agent and 70-90 parts of a polymer matrix. The modified metal nanoparticles are effectively and uniformly mixed with a macromolecular antistatic agent consisting of polyether and polyamide chain segments, so that an excellent synergistic effect can be achieved in a polymer matrix, and a complete effective conductive path is formed. The composite material can effectively form a complete conductive network under the condition of low addition amount, and the antistatic performance of the composite material is greatly improved. In addition, as the metal nanoparticles account for a small proportion of the whole antistatic fiber, the antistatic fiber is light in color, and dyeing and later processing and manufacturing are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a durable light-colored antistatic masterbatch, fiber and a preparation method thereof. Background Art

[0002] Polymer fibers have been widely used in textile, electronics, medical and other fields due to their excellent properties such as light weight, softness and corrosion resistance. However, due to their electrical insulation, polymer fibers are prone to accumulate static electricity during processing and use, which not only leads to a decline in product quality, such as dust sticking and adsorption, but also may cause a series of safety hazards, such as explosions caused by static sparks and damage to electronic equipment. Antistatic fibers effectively reduce the surface resistance of fibers by introducing conductive substances or changing the surface properties of polymer fibers, thereby inhibiting the generation and accumulation of static electricity.

[0003] Coating surfactant antistatic agents or metal cation antistatic agents on the surface of fabrics to make textiles highly hygroscopic and eliminate the accumulated charges on the surface is a common method for traditional fiber antistatic processing. However, the antistatic agent coated on the surface will be lost due to washing, so that the fabric loses its antistatic function. Adding inorganic conductive fillers to fibers is one of the most commonly used methods for preparing washable and durable antistatic fibers. By introducing metal nanoparticles (such as silver, nickel, etc.), metal oxides (such as zinc oxide, tin oxide, etc.) or carbon-based materials (such as carbon black, graphene, etc.) into the polymer matrix, a conductive network can be effectively constructed to achieve the antistatic function. However, this method has some limitations. In order to form a continuous conductive network, a large amount of conductive fillers usually need to be added, which not only increases the production cost, but also may affect the mechanical properties and processing properties of the fiber. Conductive fillers, especially carbon-based materials, have darker colors and also affect the later dyeing properties of the fiber.

[0004] In addition, polymer antistatic agents can be added to the fibers to give them long-lasting antistatic properties. Polymer antistatic agents are additives that achieve antistatic effects by reducing the volume resistivity of materials. The hydrophilic groups in their molecular structure can absorb moisture and form conductive channels, thereby effectively inhibiting the generation and accumulation of static electricity. Compared with surface-coated antistatic agents, polymer antistatic agents have the advantages of good durability, stable antistatic effects, and no influence from environmental humidity. However, in order to form an effective conductive network in the polymer matrix, a higher proportion of polymer antistatic agents is usually required. Excessive filling not only increases production costs, but also leads to poor spinnability and decreased mechanical and thermal properties of the fibers.

[0005] In summary, the introduction of conductive fillers and polymer antistatic agents has significant advantages in improving the antistatic properties of materials, but in practical applications, they still face problems such as dark color, large filling amount, and poor durability. Therefore, how to reduce the amount of fillers while ensuring light color and long-lasting antistatic effect is an urgent problem to be solved. Summary of the invention

[0006] In order to solve the above problems existing in the prior art, the present invention provides a method for preparing a durable light-colored antistatic masterbatch, and the specific preparation steps are as follows:

[0007] A durable light-colored antistatic masterbatch comprises 1-20 parts by weight of a polymer antistatic agent, 0-10 parts by weight of metal nanoparticles, 3-5 parts by weight of a dispersant, 0.3-0.5 parts by weight of a silane coupling agent, and 70-90 parts by weight of a polymer matrix.

[0008] A method for preparing a durable light-colored antistatic masterbatch comprises the following steps: placing 1-10 parts of metal nanoparticles and 1-20 parts of a high molecular antistatic agent in a vacuum drying oven respectively, and drying at a temperature of 45-80°C for 12-48 hours at a constant temperature; uniformly mixing the dried metal nanoparticles with 0.3-0.5 parts of a silane coupling agent in a blender at a temperature of 60-80°C for 10-15 minutes and a rotation speed of 30-60 rpm to obtain surface-treated metal nanoparticles; and mixing the metal nanoparticles with the dried high molecular antistatic agent and 3-5 parts of a dispersant in the blender for another 3-5 minutes; placing the composite material in a drying oven for drying after uniform blending at a drying temperature of 45-80°C, and after drying, mixing the composite material with a polymer matrix, and then adding the composite material to a parallel twin-screw extruder for melt extrusion granulation, and drying to obtain the durable light-colored antistatic masterbatch.

[0009] A durable light-colored antistatic fiber is prepared by melt spinning a durable light-colored antistatic masterbatch and polyamide 6 chips. After the durable light-colored antistatic masterbatch is dried at 100°C for 10-24 hours, the masterbatch and the polymer chips are evenly mixed and melt-spun. The spinning speed is 600-3000m / min and the initial pressure of the spinning assembly is 8-16MPa to obtain the antistatic fiber.

[0010] The outstanding substantial features and remarkable progress of the present invention are mainly reflected in that the modified metal nanoparticles are effectively mixed with the polymer antistatic agent composed of polyether and polyamide segments, and can exert excellent synergistic effects in the polymer matrix to form a complete effective conductive path. This composite material can effectively form a complete conductive network under the condition of low addition amount, and greatly improve its antistatic performance. In addition, since the proportion of metal nanoparticles in the whole antistatic fiber is not large, the antistatic fiber is light-colored, which is convenient for dyeing and later processing and manufacturing. DETAILED DESCRIPTION

[0011] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the preferred embodiments of the present invention will be described in detail below in combination with experimental data to facilitate understanding by technicians.

[0012] A durable light-colored antistatic masterbatch comprises 1-20 parts by weight of a polymer antistatic agent, 0-10 parts by weight of metal nanoparticles, 3-5 parts by weight of a dispersant, 0.3-0.5 parts by weight of a silane coupling agent, and 70-90 parts by weight of a polymer matrix.

[0013] The polymer antistatic agent is at least one of polyether amide, polyether ester and polyethylene oxide, and has a white or light yellow appearance.

[0014] The metal nanoparticles are at least one of copper powder, aluminum powder, silver powder, iron powder, zinc powder, nickel powder and tin powder, with a particle size between 300-500nm and a gray-black or metallic luster appearance.

[0015] The dispersant is 100% active polymer and has the appearance of white powder.

[0016] The silane coupling agent is selected from at least one of 1-vinyl-1,1,3,3,3-pentamethyldisiloxane, 1,3,5-trivinyl-1,1,3,5,5-pentamethyltrisiloxane, vinyltri(dimethylsiloxy)silane, 1,3-divinyltetraethoxydisiloxane, vinyltri(trimethylsiloxy)silane, vinyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane.

[0017] The polymer matrix is ​​one of polyamide 6 and polyester.

[0018] A method for preparing a durable light-colored antistatic masterbatch comprises the following steps: placing 1-10 parts of metal nanoparticles and 1-20 parts of a high molecular antistatic agent in a vacuum drying oven respectively, and drying at a temperature of 45-80°C for 12-48 hours at a constant temperature; uniformly mixing the dried metal nanoparticles with 0.3-0.5 parts of a silane coupling agent in a blender at a temperature of 60-80°C for 10-15 minutes and a rotation speed of 30-60 rpm to obtain surface-treated metal nanoparticles; and mixing the metal nanoparticles with the dried high molecular antistatic agent and 3-5 parts of a dispersant in the blender for another 3-5 minutes; placing the composite material in a drying oven for drying after uniform blending at a drying temperature of 45-80°C, and after drying, mixing the composite material with a polymer matrix, and then adding the composite material to a parallel twin-screw extruder for melt extrusion granulation, and drying to obtain the durable light-colored antistatic masterbatch.

[0019] The blending zone temperatures are 220°C, 250°C, and 250°C, respectively; the screw speed is 30-60rpm; and the blending time is 30min.

[0020] The melt extrusion granulation is as follows: the extrusion temperature of the twin-screw extruder is 220°C-260°C, the cooling temperature is 15-30°C, the screw speed is 300-500rpm; and the melt temperature is controlled at 250°C-260°C.

[0021] A durable light-colored antistatic fiber is prepared by melt spinning a durable light-colored antistatic masterbatch and polyamide 6 chips. After the durable light-colored antistatic masterbatch is dried at 100°C for 10-24 hours, the masterbatch and the polymer chips are evenly mixed and melt-spun. The spinning speed is 600-3000m / min and the initial pressure of the spinning assembly is 8-16MPa to obtain the antistatic fiber.

[0022] Embodiment 1:

[0023] A durable light-colored antistatic masterbatch comprises 20 parts by weight of a polymer antistatic agent, 0.3 parts by weight of a silane coupling agent, 1 part by weight of a metal nanoparticle, 3 parts by weight of a dispersant, and 75.7 parts by weight of a polymer.

[0024] Among them, the polymer antistatic agent is polyether amide, which has a light yellow appearance; the metal nanoparticles are nickel nanoparticles, with a particle size between 300-500nm and a gray-black appearance; the dispersant is a 100% active polymer, which has a white powder appearance; the silane coupling agent is γ-methacryloxypropyltrimethoxysilane; and the polymer matrix is ​​polyamide 6.

[0025] A method for preparing a durable light-colored antistatic masterbatch: 1 part of metal nanoparticles and 20 parts of polymer antistatic agents are placed in a vacuum drying oven respectively, and dried at a constant temperature of 80°C for 48 hours; the dried metal nanoparticles are mixed evenly with 0.3 parts of silane coupling agent in a blender at a temperature of 60-80°C, a time of 15 minutes, and a rotation speed of 30rpm to obtain surface-treated metal nanoparticles, and the metal nanoparticles are mixed with the dried polymer antistatic agent and 3 parts of dispersant in the blender for another 5 minutes. After uniform blending, the composite material is placed in a drying oven for drying at a drying temperature of 80°C, and after drying, the composite material is mixed with 75.7 parts of a polymer matrix, and then added to a parallel twin-screw extruder for melt extrusion granulation, and the durable light-colored antistatic masterbatch is obtained after drying.

[0026] Wherein, the blending is as follows: the blending zone temperatures are 220°C, 250°C, and 250°C respectively, the screw speed is 60rpm, and the blending time is 30min; the melt extrusion granulation is as follows: the extrusion temperature of the twin-screw extruder is 220°C, the cooling temperature is 30°C, and the screw speed is 500rpm; the melt temperature is controlled at 250°C.

[0027] A durable light-colored antistatic fiber is prepared by using the above-mentioned durable light-colored antistatic masterbatch. The masterbatch is dried at 100°C for 8 hours, 35 parts of the masterbatch are mixed evenly with 665 parts of polyamide 6 chips, and then melt-spun at a spinning temperature of 260°C, a spinning speed of 600m / min, and an initial pressure of the spinning assembly of 8MPa, to obtain an antistatic fiber with a spinning specification of 150D / 48f.

[0028] Embodiment 2:

[0029] A durable light-colored antistatic masterbatch comprises 20 parts by weight of a polymer antistatic agent, 0.3 parts by weight of a silane coupling agent, 0.2 parts by weight of metal nanoparticles, 3 parts by weight of a dispersant, and 76.5 parts by weight of a polymer.

[0030] Among them, the polymer antistatic agent is polyether amide, which has a light yellow appearance; the metal nanoparticles are nickel nanoparticles, with a particle size between 300-500nm and a gray-black appearance; the dispersant is a 100% active polymer, which has a white powder appearance; the silane coupling agent is γ-methacryloxypropyltrimethoxysilane; and the polymer matrix is ​​polyamide 6.

[0031] A method for preparing a durable light-colored antistatic masterbatch: 1 part of metal nanoparticles and 20 parts of polymer antistatic agents are placed in a vacuum drying oven respectively, and dried at a constant temperature of 80°C for 48 hours; the dried metal nanoparticles are mixed evenly with 0.3 parts of silane coupling agent in a blender at a temperature of 60-80°C, a time of 15 minutes, and a rotation speed of 30rpm to obtain surface-treated metal nanoparticles, and the metal nanoparticles are mixed with the dried polymer antistatic agent and 3 parts of dispersant in the blender for another 5 minutes. After uniform blending, the composite material is placed in a drying oven for drying at a drying temperature of 80°C, and after drying, the composite material is mixed with 76.5 parts of a polymer matrix, and then added to a parallel twin-screw extruder for melt extrusion granulation, and the durable light-colored antistatic masterbatch is obtained after drying.

[0032] Wherein, the blending is as follows: the blending zone temperatures are 220°C, 250°C, and 250°C respectively, the screw speed is 60rpm, and the blending time is 30min; the melt extrusion granulation is as follows: the extrusion temperature of the twin-screw extruder is 220°C, the cooling temperature is 30°C, and the screw speed is 500rpm; the melt temperature is controlled at 250°C.

[0033] A durable light-colored antistatic fiber is prepared by using the above-mentioned durable light-colored antistatic masterbatch. The masterbatch is dried at 100°C for 8 hours, 175 parts of the masterbatch and 525 parts of polyamide 6 chips are mixed evenly and then melt-spun at a spinning temperature of 260°C, a spinning speed of 600m / min, and an initial pressure of the spinning assembly of 8MPa to obtain an antistatic fiber with a spinning specification of 150D / 48f.

[0034] Embodiment 3:

[0035] A durable light-colored antistatic masterbatch comprises 20 parts by weight of a polymer antistatic agent, 0.3 parts by weight of a silane coupling agent, 0.1 parts by weight of metal nanoparticles, 3 parts by weight of a dispersant, and 76.6 parts by weight of a polymer.

[0036] Among them, the polymer antistatic agent is polyether amide, which has a light yellow appearance; the metal nanoparticles are nickel nanoparticles, with a particle size between 300-500nm and a gray-black appearance; the dispersant is a 100% active polymer, which has a white powder appearance; the silane coupling agent is γ-methacryloxypropyltrimethoxysilane; and the polymer matrix is ​​polyamide 6.

[0037] A method for preparing a durable light-colored antistatic masterbatch: 0.1 parts of metal nanoparticles and 20 parts of polymer antistatic agents are placed in a vacuum drying oven respectively, and dried at a constant temperature of 80°C for 48 hours; the dried metal nanoparticles are mixed evenly with 0.3 parts of silane coupling agent in a blender at a temperature of 60-80°C, a time of 15 minutes, and a rotation speed of 30rpm to obtain surface-treated metal nanoparticles, and the metal nanoparticles are mixed with the dried polymer antistatic agent and 3 parts of dispersant in the blender for another 5 minutes. After uniform blending, the composite material is placed in a drying oven for drying at a drying temperature of 80°C, and after drying, the composite material is mixed with 76.6 parts of a polymer matrix, and then added to a parallel twin-screw extruder for melt extrusion granulation, and the durable light-colored antistatic masterbatch is obtained after drying.

[0038] Wherein, the blending is as follows: the blending zone temperatures are 220°C, 250°C, and 250°C respectively, the screw speed is 60rpm, and the blending time is 30min; the melt extrusion granulation is as follows: the extrusion temperature of the twin-screw extruder is 220°C, the cooling temperature is 30°C, and the screw speed is 500rpm; the melt temperature is controlled at 250°C.

[0039] A durable light-colored antistatic fiber is prepared by using the above-mentioned durable light-colored antistatic masterbatch. The masterbatch is dried at 100°C for 8 hours, 350 parts of the masterbatch and 350 parts of polyamide 6 chips are mixed evenly and then melt-spun at a spinning temperature of 260°C, a spinning speed of 600m / min, and an initial pressure of the spinning assembly of 8MPa to obtain an antistatic fiber with a spinning specification of 150D / 48f.

[0040] Embodiment 4:

[0041] A durable light-colored antistatic masterbatch comprises 20 parts by weight of a polymer antistatic agent, 0.3 parts by weight of a silane coupling agent, 0.1 parts by weight of metal nanoparticles, 3 parts by weight of a dispersant, and 76.6 parts by weight of a polymer.

[0042] Among them, the polymer antistatic agent is polyether amide, which has a light yellow appearance; the metal nanoparticles are silver nanoparticles, with a particle size between 300-500nm and a grayish yellow appearance; the dispersant is a 100% active polymer, which has a white powder appearance; the silane coupling agent is γ-methacryloxypropyltrimethoxysilane; and the polymer matrix is ​​polyamide 6.

[0043] A method for preparing a durable light-colored antistatic masterbatch: 0.1 parts of metal nanoparticles and 20 parts of polymer antistatic agents are placed in a vacuum drying oven respectively, and dried at a constant temperature of 80°C for 48 hours; the dried metal nanoparticles are mixed evenly with 0.3 parts of silane coupling agent in a blender at a temperature of 60-80°C, a time of 15 minutes, and a rotation speed of 30rpm to obtain surface-treated metal nanoparticles, and the metal nanoparticles are mixed with the dried polymer antistatic agent and 3 parts of dispersant in the blender for another 5 minutes. After uniform blending, the composite material is placed in a drying oven for drying at a drying temperature of 80°C, and after drying, the composite material is mixed with 76.6 parts of a polymer matrix, and then added to a parallel twin-screw extruder for melt extrusion granulation, and the durable light-colored antistatic masterbatch is obtained after drying.

[0044] Wherein, the blending is as follows: the blending zone temperatures are 220°C, 250°C, and 250°C respectively, the screw speed is 30rpm, and the blending time is 30min; the melt extrusion granulation is as follows: the extrusion temperature of the twin-screw extruder is 220°C, the cooling temperature is 30°C, and the screw speed is 500rpm; the melt temperature is controlled at 250°C.

[0045] A durable light-colored antistatic fiber is prepared by using the above-mentioned durable light-colored antistatic masterbatch. The masterbatch is dried at 100°C for 8 hours, 350 parts of the masterbatch and 350 parts of polyamide 6 chips are mixed evenly and then melt-spun at a spinning temperature of 260°C, a spinning speed of 600m / min, and an initial pressure of the spinning assembly of 8MPa to obtain an antistatic fiber with a spinning specification of 150D / 48f.

[0046] Embodiment 5:

[0047] A durable light-colored antistatic masterbatch comprises 20 parts by weight of a polymer antistatic agent, 0.3 parts by weight of a silane coupling agent, 0.1 parts by weight of metal nanoparticles, 3 parts by weight of a dispersant, and 76.6 parts by weight of a polymer.

[0048] Among them, the polymer antistatic agent is polyether amide, which has a light yellow appearance; the metal nanoparticles are nickel nanoparticles, with a particle size between 300-500nm and a gray-black appearance; the dispersant is a 100% active polymer, which has a white powder appearance; the silane coupling agent is γ-methacryloxypropyltrimethoxysilane; and the polymer matrix is ​​polyester.

[0049] A method for preparing a durable light-colored antistatic masterbatch: 0.1 parts of metal nanoparticles and 20 parts of polymer antistatic agents are placed in a vacuum drying oven respectively, and dried at a constant temperature of 80°C for 48 hours; the dried metal nanoparticles are mixed evenly with 0.3 parts of silane coupling agent in a blender at a temperature of 60-80°C, a time of 15 minutes, and a rotation speed of 30rpm to obtain surface-treated metal nanoparticles, and the metal nanoparticles are mixed with the dried polymer antistatic agent and 3 parts of dispersant in the blender for another 5 minutes. After uniform blending, the composite material is placed in a drying oven for drying at a drying temperature of 80°C, and after drying, the composite material is mixed with 76.6 parts of a polymer matrix, and then added to a parallel twin-screw extruder for melt extrusion granulation, and the durable light-colored antistatic masterbatch is obtained after drying.

[0050] Wherein, the blending is as follows: the blending zone temperatures are 220°C, 250°C, and 250°C respectively, the screw speed is 60rpm, and the blending time is 30min; the melt extrusion granulation is as follows: the extrusion temperature of the twin-screw extruder is 220°C, the cooling temperature is 30°C, and the screw speed is 500rpm; the melt temperature is controlled at 250°C.

[0051] A durable light-colored antistatic fiber is prepared by using the above-mentioned durable light-colored antistatic masterbatch. The masterbatch is dried at 100°C for 8 hours, 350 parts of the masterbatch and 350 parts of polyester chips are mixed evenly and then melt-spun at a spinning temperature of 260°C, a spinning speed of 600m / min, and an initial pressure of the spinning assembly of 8MPa to obtain an antistatic fiber with a spinning specification of 150D / 48f.

[0052] Embodiment 6:

[0053] A durable light-colored antistatic masterbatch comprises 20 parts by weight of a polymer antistatic agent, 0.3 parts by weight of a silane coupling agent, 0.2 parts by weight of metal nanoparticles, 3 parts by weight of a dispersant, and 76.5 parts by weight of a polymer.

[0054] Among them, the polymer antistatic agent is polyether amide, which has a light yellow appearance; the metal nanoparticles are nickel nanoparticles, with a particle size between 300-500nm and a gray-black appearance; the dispersant is a 100% active polymer, which has a white powder appearance; the silane coupling agent is γ-methacryloxypropyltrimethoxysilane; and the polymer matrix is ​​polyamide 6.

[0055] The durable light-colored antistatic masterbatch, fiber and preparation method thereof are as follows: 0.2 parts of metal nanoparticles and 20 parts of polymer antistatic agent are placed in a vacuum drying oven respectively, and dried at a constant temperature of 80°C for 48 hours; the dried metal nanoparticles are mixed evenly with 0.3 parts of silane coupling agent in a blender at a temperature of 60-80°C, a time of 15 minutes, and a speed of 30rpm to obtain surface-treated metal nanoparticles, and the metal nanoparticles are mixed with the dried polymer antistatic agent and 3 parts of dispersant in the blender for another 5 minutes. After uniform blending, the composite material is placed in a drying oven for drying at a drying temperature of 80°C, and after drying, the composite material is mixed with 76.5 parts of a polymer matrix and then added to a parallel twin-screw extruder for melt extrusion granulation, and the durable light-colored antistatic masterbatch is obtained after drying.

[0056] Wherein, the blending is as follows: the blending zone temperatures are 220°C, 250°C, and 250°C respectively, the screw speed is 60rpm, and the blending time is 30min; the melt extrusion granulation is as follows: the extrusion temperature of the twin-screw extruder is 220°C, the cooling temperature is 30°C, and the screw speed is 500rpm; the melt temperature is controlled at 250°C.

[0057] A durable light-colored antistatic fiber is prepared by using the above-mentioned durable light-colored antistatic masterbatch. The masterbatch is dried at 100°C for 8 hours, 350 parts of the masterbatch and 350 parts of polyamide 6 chips are mixed evenly and then melt-spun at a spinning temperature of 260°C, a spinning speed of 600m / min, and an initial pressure of the spinning assembly of 8MPa to obtain an antistatic fiber with a spinning specification of 150D / 48f.

[0058] Embodiment 7:

[0059] A durable light-colored antistatic masterbatch comprises 20 parts by weight of a polymer antistatic agent, 0.3 parts by weight of a silane coupling agent, 0.3 parts by weight of a metal nanoparticle, 3 parts by weight of a dispersant, and 76.4 parts by weight of a polymer.

[0060] Among them, the polymer antistatic agent is polyether amide, which has a light yellow appearance; the metal nanoparticles are nickel nanoparticles, with a particle size between 300-500nm and a gray-black appearance; the dispersant is a 100% active polymer, which has a white powder appearance; the silane coupling agent is γ-methacryloxypropyltrimethoxysilane; and the polymer matrix is ​​polyamide 6.

[0061] A method for preparing a durable light-colored antistatic masterbatch: 0.3 parts of metal nanoparticles and 20 parts of polymer antistatic agents are placed in a vacuum drying oven respectively, and dried at a constant temperature of 80°C for 48 hours; the dried metal nanoparticles are mixed evenly with 0.3 parts of silane coupling agent in a blender at a temperature of 60-80°C, a time of 15 minutes, and a rotation speed of 30rpm to obtain surface-treated metal nanoparticles, and the metal nanoparticles are mixed with the dried polymer antistatic agent and 3 parts of dispersant in the blender for another 5 minutes. After uniform blending, the composite material is placed in a drying oven for drying at a drying temperature of 80°C, and after drying, the composite material is mixed with 76.6 parts of a polymer matrix, and then added to a parallel twin-screw extruder for melt extrusion granulation, and the durable light-colored antistatic masterbatch is obtained after drying.

[0062] Wherein, the blending is as follows: the blending zone temperatures are 220°C, 250°C, and 250°C respectively, the screw speed is 60rpm, and the blending time is 30min; the melt extrusion granulation is as follows: the extrusion temperature of the twin-screw extruder is 220°C, the cooling temperature is 30°C, and the screw speed is 500rpm; the melt temperature is controlled at 250°C.

[0063] A durable light-colored antistatic fiber is prepared using the above-mentioned durable light-colored antistatic masterbatch. The masterbatch is dried at 100°C for 8 hours, 350 parts of the masterbatch and 350 parts of polyamide 6 chips are mixed evenly and melt-spun at a spinning temperature of 260°C, a spinning speed of 600m / min, and an initial pressure of the spinning assembly of 8MPa to obtain an antistatic fiber with a spinning specification of 150D / 48f. Performance test:

[0064] Surface resistivity test: The test method refers to the standard GB 12014-2019 standard method test for anti-static clothing, unit: Ω;

[0065] Fabric washing: The test method refers to the standard GB / T 8629-2017 Household washing and drying procedures for textile testing;

[0066] Fabric whiteness: The test method refers to the standard GB / T 17644-2008 Test method for whiteness and chromaticity of textile fibers, unit: %.

[0067] See the table below for details

[0068]

[0069] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A durable light-colored antistatic masterbatch, characterized in that: The invention comprises 1-20 parts by weight of a polymer antistatic agent, 0-10 parts by weight of metal nanoparticles, 3-5 parts by weight of a dispersant, 0.3-0.5 parts by weight of a silane coupling agent and 70-90 parts by weight of a polymer matrix.

2. The durable light-colored antistatic masterbatch according to claim 1, characterized in that: The polymer antistatic agent is at least one of polyether amide, polyether ester and polyethylene oxide, and has a white or light yellow appearance.

3. The durable light-colored antistatic masterbatch according to claim 1, characterized in that: The metal nanoparticles are at least one of copper powder, aluminum powder, silver powder, iron powder, zinc powder, nickel powder and tin powder, with a particle size between 300-500nm and a gray-black or metallic luster appearance.

4. The durable light-colored antistatic masterbatch according to claim 1, characterized in that: The dispersant is 100% active polymer and has the appearance of white powder.

5. The durable light-colored antistatic masterbatch according to claim 1, characterized in that: The silane coupling agent is selected from at least one of 1-vinyl-1,1,3,3,3-pentamethyldisiloxane, 1,3,5-trivinyl-1,1,3,5,5-pentamethyltrisiloxane, vinyltri(dimethylsiloxy)silane, 1,3-divinyltetraethoxydisiloxane, vinyltri(trimethylsiloxy)silane, vinyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane.

6. The durable light-colored antistatic masterbatch according to claim 1, characterized in that: The polymer matrix is ​​one of polyamide 6 and polyester.

7. A method for preparing the durable light-colored antistatic masterbatch according to any one of claims 1 to 6, characterized in that 1-10 parts of metal nanoparticles and 1-20 parts of polymer antistatic agent are placed in a vacuum drying oven, and dried at a constant temperature of 45-80°C for 12-48 hours; the dried metal nanoparticles are mixed evenly with 0.3-0.5 parts of silane coupling agent in a blender at a temperature of 60-80°C for 10-15 minutes. The metal nanoparticles are mixed with the dried polymer antistatic agent and 3-5 parts of dispersant in a blender for 3-5 minutes at a speed of 30-60 rpm to obtain surface-treated metal nanoparticles; the metal nanoparticles are mixed with the dried polymer antistatic agent and 3-5 parts of dispersant in a blender for another 3-5 minutes; after uniform blending, the composite material is placed in a drying oven for drying at a temperature of 45-80°C; after drying, the composite material is mixed with a polymer matrix and added into a parallel twin-screw extruder for melt extrusion granulation; after drying, the durable light-colored antistatic masterbatch is obtained.

8. The method for preparing the durable light-colored antistatic masterbatch according to claim 7, characterized in that: The blending is as follows: the blending zone temperatures are 220° C., 250° C., and 250° C. respectively, the screw speed is 30-60 rpm, and the blending time is 30 min.

9. The method for preparing the durable light-colored antistatic masterbatch according to claim 7, characterized in that: The melt extrusion granulation is as follows: the extrusion temperature of the twin-screw extruder is 220-260°C, the cooling temperature is 15-30°C, the screw speed is 300-500rpm; and the melt temperature is controlled at 250-260°C.

10. A durable light-colored antistatic fiber, characterized in that The durable light-colored antistatic masterbatch according to any one of claims 1 to 6 is prepared by melt spinning with polyamide 6 chips. After the durable light-colored antistatic masterbatch is dried at 100°C for 10-24 hours, the masterbatch and the polymer chips are evenly mixed and melt-spun. The spinning speed is 600-3000m / min and the initial pressure of the spinning assembly is 8-16MPa to obtain antistatic fibers.

Citation Information

Patent Citations

  • Production method of high-performance conductive fiber

    CN102766987A

  • Antistatic master batch for polyester

    CN103709653A

Cited By

  • Special color master batch for high-efficiency cool chinlon and preparation method of special color master batch

    CN120904675A

  • High-efficiency cool-feeling nylon special color master batch and preparation method thereof

    CN120904675B